2011
DOI: 10.5402/2011/393891
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organizing Map-Based Color Image Segmentation with k-Means Clustering and Saliency Map

Abstract: Natural image segmentation is an important topic in digital image processing, and it could be solved by clustering methods. We present in this paper an SOM-based k-means method (SOM-K) and a further saliency map-enhanced SOM-K method (SOM-KS). In SOM-K, pixel features of intensity and L∗u∗v∗ color space are trained with SOM and followed by a k-means method to cluster the prototype vectors, which are filtered with hits map. A variant of the proposed method, SOM-KS, adds a modified saliency map to improve the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…SOM is regarded as a specific region-based image segmentation technique by [28]. SOM combined with K -means has achieved better segmentation results in natural color image segmentation compared to JSEG, which is one of the most used techniques for segmentation based on regions of images taken under natural (uncontrolled) conditions [29]. The SOM training generates a map with output neurons, where each neuron represents a color group.…”
Section: Sevue Methodologymentioning
confidence: 99%
“…SOM is regarded as a specific region-based image segmentation technique by [28]. SOM combined with K -means has achieved better segmentation results in natural color image segmentation compared to JSEG, which is one of the most used techniques for segmentation based on regions of images taken under natural (uncontrolled) conditions [29]. The SOM training generates a map with output neurons, where each neuron represents a color group.…”
Section: Sevue Methodologymentioning
confidence: 99%
“…However, it has been observed that every clustering index cannot be applied in every sector of clustering application. Clustering in remotely sensed images can be correctly evaluated by the DB index [42,43] and it is noted that the DB index is used in combining with another index in the unsupervised classification method [42,44]. However, DB index [40] works efficiently only for spherical clusters [45] though it is very much noise sensitive.…”
Section: Endmentioning
confidence: 98%
“…. So presenting repeatedly the training patterns tries to make the synaptic weight vectors tend to follow the ordination of the input patterns [7,8,9].…”
Section: A Self Organizing Feature Mapmentioning
confidence: 99%